Selection of Suitable Sites for Small Ruminant Production Using Remote Sensing and the Geographic Information System - Halil Baki Ünal; Esin Deri (Journal of Agricultural Sciences)
The aim of this study was to determine the most suitable areas for small ruminant production in the Karaburunarea in Izmir province, Turkey. To this purpose, an inquiry model was first developed using remote sensing and ageographic information system. In developing the model, legal and technical factors were taken into consideration,and eight evaluation criteria (distance from settled areas, distance from lakes or similar water sources, distance fromprotected water catchment basins, distance from wind energy generators, distance from irrigation and drainage canals,slope, aspect-direction of slope-and land use class) and three evaluation classes in relation to these criteria (suitable,conditionally suitable and unsuitable) were planned. Later, the model was used to test the suitability of the study areain general and five sample farms in that area for suitability. According to all of the criteria of evaluation, 3.54% of the42,707.15 ha study area was found to be suitable for small ruminant production, 2.78% was conditionally suitable, and93.60% was unsuitable. As for the five sample farms in the study area, none of them was found to be suitable accordingto all of the evaluation criteria. In addition, suggestions were made for the functionality and effectiveness in use of thegeography information inquiry models used in the choice of places for small ruminant production.